Statistical mechanics of surfaces - Hemingway, S; Hemingway, Stephen (1982)
﻿ The equilibrium properties of a spherical drop are investigated using the penetrable-sphere model of a fluid. To estimate the surface tension, a new statistical mechanical formula, the extension of the Triezenberg-Zwanzig result for a planar surface, is derived. The density profiles for use in this are obtained from an integral equation expressing the constancy of chemical potential through the interface. Numerical solutions can be obtained and from these numerical estimates for the surface tension. They are in good agreement with estimates from an independent thermodynamic route. These routes, as well as a further, zero-temperature, exact, analytic one, show that the surface tension of this model increases with decreasing drop size. The planar surface of the model is also briefly investigated using a well-known integrodifferential equation. Two approximations are made for the direct correlation function, one a systematic improvement on the other. They yield solutions for the density profile of a limited range of temperatures below the critical point. When the direct correlation function of a Lennard-Jones fluid is approximated the resulting equation for the profile resists numerical solution.